What role does multisensory integration play in the visuotactile perception of texture? - Guest, S; Spence, C (2003)
Previous research has shown that vision and touch are both effective at many roughness discrimination tasks; however, there is no evidence that using both senses simultaneously improves discrimination performance. We investigated the nature of this failure to integrate multisensory inputs, using three varieties of forced-choice discrimination tasks. In Experiment 1, visual, tactile and bimodal roughness discriminations were made between pairs of fabric stimuli. Bimodal discriminations were typically performed with a sensitivity somewhere between that observed for the unimodal presentations. In Experiment 2, a similar design was used except that during the stimulus presentation, one interval contained a unimodal (vision or touch) stimulus, the other interval a bimodal stimulus presentation. Bias toward the bimodal interval would indicate an increase in the magnitude of perceived roughness for such presentations. No such bias was found. In Experiment 3, participants made single-interval, bimodal discriminations, determining whether a rough stimulus was presented to touch, to vision, to both modalities, or to neither modality. The improved performance seen for the dual-target vs. single-target presentations was best modelled as arising from a trialwise division of attention between vision and touch. Overall, these results suggest that vision and touch act as independent sources of roughness information, where the necessity to divide attention across both modalities reduces the discriminative ability in (or information available from) each of these individual modalities.